Exploring Influential Factors in Engineering Students’ Adoption of Mobile-Based Gamified Learning - Candra, Oriza; Yanto, Doni Tri Putra; Zaswita, Hermi; Samala, Agariadne Dwinggo; Rawas, Soha; Ulibarrena, Juana Maria Arcelus (International Journal of Online and Biomedical Engineering (iJOE), 2026)
Gamification in education has gained increasing popularity as a means to promote quality education, particularly when integrated with mobile technology to create engaging and accessible learning environments that align with technological advancements. However, a more comprehensive understanding is needed regarding students’ acceptance of such technology, especially in the context of the electrical machinery course. This study investigates students’ acceptance of mobile-based gamified learning (MoGaLearn) in the instruction of electrical machinery. Student acceptance is assessed through the actual use (AU) variable, based on the technology acceptance model (TAM) framework. The theoretical model employed includes key determinants such as perceived ease of use (PEU), perceived usefulness (PU), attitude toward use (A), and behavioral intention (BI). A quantitative, survey-based approach was adopted, involving 136 engineering students who completed a structured questionnaire. Data were analyzed using variance-based structural equation modeling (VB-SEM). The findings reveal that students of the Industrial Electrical Engineering program demonstrate a high level of acceptance toward MoGaLearn in the electrical machinery course. The constructs PEU, PU, A, and BI were empirically found to have a positive and significant influence on students’ acceptance of MoGaLearn. These results highlight the importance of considering these factors in the design, development, selection, and implementation of gamification learning tools in engineering education.